Development of a novel instrument for assessing intentional non-adherence to official medical recommendations (iNAR-12): a sequential mixed-methods study in Serbia - S Stankovic; M Ninkovic; M Zivanovic; D Purić; M B Petrović; P Lukić; Z Zupan; M Branković; L B Lazarević; I Žeželj (BMJ Open, 2023)
Objectives We aimed to (1) develop a novel instrument, suitable for the general population, capturing intentional non-adherence (iNAR), consisting of non-adherence to prescribed therapy, self-medication and avoidance of seeking medical treatment; (2) differentiate it from other forms of non-adherence, for example, smoking; and (3) relate iNAR to patient-related factors, such as sociodemographics, health status and endorsement of irrational beliefs (conspiratorial thinking and superstitions) and to healthcare-related beliefs and experiences ((mis)trust and negative experiences with the healthcare system, normalisation of patient passivity).Design То generate iNAR items, we employed a focus group with medical doctors, supplemented it with a literature search and invited a public health expert to refine it further. We examined the internal structure and predictors of iNAR in an observational study.Setting Data were collected online using snowball sampling and social networks.Participants After excluding those who failed one or more out of three attention checks, the final sample size was n=583 adult Serbian citizens, 74.4% female, mean age 39.01 years (SD=12.10).Primary and secondary outcome measures The primary, planned outcome is the iNAR Questionnaire, while smoking was used for comparison purposes.Results Factor analysis yielded a one-factor solution, and the final 12-item iNAR Questionnaire had satisfactory internal reliability (alpha=0.72). Health condition and healthcare-related variables accounted for 14% of the variance of iNAR behaviours, whereas sociodemographics and irrational beliefs did not additionally contribute.Conclusions We constructed a brief yet comprehensive measure of iNAR behaviours and related them to health and sociodemographic variables and irrational beliefs. The findings suggest that public health interventions should attempt to improve patients' experiences with the system and build trust with their healthcare practitioners rather than aim at specific demographic groups or at correcting patients’ unfounded beliefs.Study registration The design and confirmatory analyses plan were preregistered (https://osf.io/pnugm).